2015
DOI: 10.3748/wjg.v21.i41.11522
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory status in human hepatic cirrhosis

Abstract: This review focuses on new findings about the inflammatory status involved in the development of human liver cirrhosis induced by the two main causes, hepatitis C virus (HCV) infection and chronic alcohol abuse, avoiding results obtained from animal models. When liver is faced to a persistent and/or intense local damage the maintained inflammatory response gives rise to a progressive replacement of normal hepatic tissue by non-functional fibrotic scar. The imbalance between tissue regeneration and fibrosis wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 195 publications
3
51
0
7
Order By: Relevance
“…AB also may induce inflammation by programming liver macrophages (Kupffer cells) toward a proinflammatory phenotype. This, in turn, would promote the uptake of virus by hepatocytes (16) and finally contribute to cirrhosis/HCC development (32). The regulation of a cytokine profile of dendritic cells phagocytosed HCV ϩ AB was reported before (59).…”
Section: Discussionmentioning
confidence: 88%
“…AB also may induce inflammation by programming liver macrophages (Kupffer cells) toward a proinflammatory phenotype. This, in turn, would promote the uptake of virus by hepatocytes (16) and finally contribute to cirrhosis/HCC development (32). The regulation of a cytokine profile of dendritic cells phagocytosed HCV ϩ AB was reported before (59).…”
Section: Discussionmentioning
confidence: 88%
“…Alcohol-related cirrhosis causes a stronger inflammatory response resulting in problems controlling the immune system, compared to viral-related cirrhosis[26]. Among patients who were hospitalized due to complications of cirrhosis, alcohol-related cirrhosis was the predominant cause[27].…”
Section: Discussionmentioning
confidence: 99%
“…[53] Consequently, The predominant features of HCV-C are more related with those that allow viral evasion of the immune defenses, especially although not exclusively, inhibition of interferons secretion, natural killer cells activation and T cell-mediated cytotoxicity. [54] Several researchers have suggested that an adequate T-helper 1 (Th1) response [i.e. high interferon (IFN)-γ secretion by peripheral blood mononuclear cells] may be associated with a protective antiviral immune response, [55] while insufficient systemic Th1 cytokine secretion may be associated with increased viral load and disease progression.…”
Section: Structural Organization Of the Liver And Cytokines Potentialmentioning
confidence: 99%